STUDY OF HEPATOPROTECTIVE ACTIVITY OF STINGLESS BEE PROPOLIS AGAINTS TOXICITY OF DRUGS - MAHANI; GREGORIUS A O B; ENDAH WULANDARI; AHMAD SULAEMAN; HARDINSYAH; NUNUNG NURJANAH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of this study is to determine the effect of stingless bee propolis supplementation as a hepatoprotector on the prevention of DILI and the effect of healing and restoring nutrition for DILI patients due to drug induction. Methods: The literature review starts from problem identification, library data collection, reading, taking notes, analyzing, and processing the data obtained and then compiling it into a systematic review Results: The results of a literature study conducted show that propolis has a good hepatoprotective ability against drugs that cause DILI cases such as the anti-tuberculosis, antibiotic and antipyretic groups as indicated by the SGPT, SGOT, BT, GSH, and SOD values that are close to normal values. In addition, propolis supplementation can accelerate the healing and restoration of the nutritional status of DILI patients. All active compounds contained in propolis such as phytochemicals and lipopolysaccharides work to protect the liver from the toxic effects of DILI through antioxidant mechanisms. Conclusion: Overall, the data from this literature study show that the hepatoprotective activity of propolis has the potential to complement drug therapy to reduce hepatotoxic effects and can conclusively beneficial to accelerate the restoration of nutritional status for DILI patients.